Characterization of carotenoid pigments in amphibian, Rhacophorous bipunctatus - Baruah, Pinky; UC, Goswami (Journal of Research in Biology, 2012)
Pigmentation has attracted human beings from time immemorial. Various pigmentations and their orientation are a matter of curiosity regarding their occurrence, metabolism as well as functional properties. Several issues has been discussed and referred as cited by earlier workers on the diversity of piscian and amphibian species showing magnificent colouration, their chemistry, physiology as well as metabolic transformation and more, especially on the existence of different retinoid molecules. Animals use different types of pigments to acquire their colourful ornaments. Knowing the types of pigments that generate animal colours often provide valuable information about the costs of developing bright coloration as well as the benefits of using these signals in social or sexual contexts. Within the various classes of natural pigments, the carotenoids are the most widespread and structurally diverse pigmenting agents. Many animals use carotenoid pigments to colour their integument red, orange, or yellow (Fox, 1976). Carotenoids are a family of over 600 natural lipid-soluble pigments that are produced within microalgae, phytoplankton, and higher plants. Thus to study the carotenoid profile, R.bipunctatus, a small brilliantly coloured tree frog, was selected and collected. The carotenoids profile from the entire skin was analysed through HPLC. Carotenoids such as astaxanthin, β-carotene, cryptoxanthin, lutein, zeaxanthin were present in the amphibian species of the present study